INFLUENCE OF «IT» AND MODERN EQUIPMENT ON THE TECHNOLOGY OF RESTAURANT PRODUCTION IN THE CONDITIONS OF IMPLEMENTATION OF HACCP (Development Service Industry Management, 2025)
Тhe article examines the impact of information technologies and modern equipment on the production technology of restaurant products under the conditions of the implementation of the HACCP system. The authors note that in the conditions of rapid technological development and increasing requirements for food safety, the HACCP system (Hazard Analysis and Critical Control Points) is becoming an integral part of quality control and product safety. The restaurant business, which operates in accordance with new standards, must adapt its technological processes, including the use of the latest information technologies and high-tech equipment.The study examines the main aspects that ensure the efficiency of technological processes in the restaurant industry. In particular, the impact of innovative information systems on the optimization of production processes and ensuring food safety is investigated. Information technologies and process automation can significantly reduce the likelihood of errors and provide a high level of monitoring of critical points responsible for the quality and safety of products.The study also analyzes the role of modern equipment in improving production technology in the restaurant business. High-precision technologies, automated systems and modern equipment allow for more effective control of product quality at all stages of production. The implementation of such technologies requires appropriate personnel qualifications and adaptation of production processes to new conditions.The authors note that one of the key aspects is the relationship between digital tools, technical innovations and the effectiveness of implementing HACCP principles. The integration of modern software solutions into the production processes of restaurant establishments provides automated management of critical points and timely detection of violations, which allows significantly reducing risks and ensuring compliance with safety standards.As a result of the study, the authors proposed practical recommendations for integrating the latest technologies into restaurant processes, which will contribute to increasing the level of safety and product quality. Prospects for further research are related to a more in-depth study of the impact of automation and digitalization on the effectiveness of HACCP system management, as well as the development of new tools to improve control over production processes in the industry.
Keywords: equipment; information technology; product technology; restaurant industry; HACCP system; food safety; production process; product quality